Experimental study on micro-damage of rock under rheological disturbance - Bo WANG; Yongzheng REN; Zhiyin TIAN; Shiji MA; Jun WANG; Wanpeng HUANG; Ling WANG (Meitan xuebao)
High in-situ stress and mining disturbance will lead to the deformation and instability of deep rock mass. Under the action of high in-situ stress, deep rock mass enters the strength limit neighborhood, and the rock mass entering the strength limit neighborhood is very sensitive to mining disturbance. Research on micro-damage test of rock rheological disturbance effect is the key to solve the problem. In order to meet the test requirements in the research process, a micro-damage test system for rock rheological disturbance effect was developed. The test system optimized the host of the tester by upgrading the disturbance loading device, and expanded the micro-damage test function of rock rheological disturbance effect. The test results show that: ① The performance of rock rheological disturbance effect micro-damage test system is reliable, which is suitable for the related research of rock rheological disturbance effect micro-damage test; ② When the rock enters the strength limit neighborhood, the growth rate of large-sized pores with a pore size greater than 1 μm is much larger than the growth rate and pore compaction amplitude of small-sized pores with a pore size less than 1 μm, resulting in irreversible damage inside the rock; ③ Under different confining pressure rheological disturbance conditions, when the specimen is outside the strength limit neighborhood, the confining pressure has a certain inhibitory effect on the expansion and development of the pores of the specimen, and the compaction amplitude of the pores inside the specimen is greater than its expansion amplitude. With the increase of confining pressure, when entering the strength limit neighborhood, the existence of confining pressure accelerates the expansion and development of pores to a certain extent, and the internal pores of the specimen are dominated by expansion and development; ④ The microscopic criterion for the rock to enter the strength limit neighborhood is determined, that is, when the proportion of large-sized pores with pore size greater than 1μm increases significantly under the condition of rheological disturbance, it indicates that the rock has entered the strength limit neighborhood.